When a=0, b=-1 find the value of the given expressions:

(i) 2a + 2b

(ii) 2a^{2} + b^{2}+1

(iii) 2a^{2}b + 2ab^{2} + ab

(iv) a^{2} + ab +2

(i) 2a + 2b

Put a = 0 and b = -1

= 2(0) + 2(-1)

= 0 - 2

= -2

(ii) 2a^{2} + b^{2} +1

Put a = 0 and b = -1

= 2(0)^{2} + (-1)^{2} + 1

=2(0) + 1 + 1

=0 + 1 + 1

=1

(iii)2a^{2}b + 2ab^{2} + ab

Put a = 0 and b = -1

= 2(0)^{2}(-1) + 2(0)(-1)^{2} + 0(-1)

=2(0)(-1) + 2(0)(1) + 0

=0 + 0 + 0

=0

(iv) a^{2} + ab + 2

Put a = 0 and b = -1

=(0)^{2} + 0(-1) + 2

= 0 + 0 + 2

=2

11